Laboratory Diagnosis of Tuberculosis- an Update - Ahammad, Faruk; Hossain, Ahmed Manadir; Siddique, Mohammad Abu Bakar; Biswas, Nipendra Nath (Faridpur Medical College Journal, 2016)
Annually about two million deaths occur globally due to tuberculosis (TB). Bangladesh ranks the sixth position among 22 highest burden TB countries in the world and also one of the 27 high multidrug resistant tuberculosis (MDR-TB) burden countries where about 70,000 people die every year due to TB. Among six key components of Stop TB Strategy (STS) Plan, the first one includes increase case notification of all forms of TB and improve diagnosis of new smear negative, extrapulmonary cases and TB in children by 2016. As TB can affect any organ in human body, the TB cases are managed by any discipline in medical community. Unfortunately diagnostic accuracy is not satisfactory and is not only due to uniform unavailability of the latest diagnostic facilities but also due to inadequate knowledge of the professionals about currently available modern laboratory techniques to diagnose TB. Light-emitting diode (LED) microscopy with fluorescence (auramine-rhodamine staining) should be preferred than conventional microscopy with Zeihl-neelsen (acid fast) staining to identify TB bacilli. Mantoux test (MT) indicates only infection by TB bacilli, does not necessarily the active disease. It may be positive in latent TB and in BCG (Bacillus Calmette-Guerin) vaccinated cases. Antibodies from Lymphocyte Secretion or Antibodies in Lymphocyte Supernatant (ALS) assay can detect active TB cases within three days of sample collection. The test is very useful to diagnose TB in children where sputum collection is difficult. Interferon gamma release assay (IGRA) tests are not advocated in low and middle-income countries, typically those with a high TB and/or HIV burden. Anti TB IgG/IgM/IgA tests should be avoided because these are being misinterpreted by someone as active TB cases. Adenosine Deaminase Assay (ADA) is a reliable test to diagnose tuberculous pleural effusion together with other evidences. ADA in pleural fluid <40 IU/L is considered negative for TB. The more the ADA level, the more possibility to be tuberculous effusion. Level >100 IU/L is highly specific for TB origin. Gene Xpert MTB/RIF, an Xpert test for mycobacterium tuberculosis (MTB) and Rifampicin (RIF) resistance, is used for rapid identification for TB bacilli, specially when MDR-TB is suspected, in human immunodeficiency virus ( HIV) infected cases and highly suspected sputum negative cases ( as a follow on test ) where microscopy frequently failed due to low bacterial load. The test exhibits high sensitivity and specificity for detecting pulmonary TB. Faridpur Med. Coll. J. Jul 2015;10(2): 71-75